Cono‐spondylar dysplasia: Clinical, radiographic, and molecular findings of a previously unreported disorder. Issue 9 (26th June 2014) - Ben‐Omran, Tawfeg; Lakhani, Shenela; Almureikhi, Mariam; Ali, Rehab; Takahashi, Atsushi; Miyake, Noriko; Matsumoto, Naomichi; Ikegawa, Shiro; Superti‐Furga, Andrea; Unger, Sheila
<x xml:space="preserve">Abstract</x> We report on a consanguineous Arab family in which three sibs had an unusual skeletal dysplasia characterized by anterior defects of the spine leading to severe lumbar kyphosis and marked brachydactyly with cone epiphyses. The clinical phenotype also included dysmorphic facial features, epilepsy, and developmental delay. This constellation likely represents a previously undescribed skeletal dysplasia, most probably inherited in an autosomal recessive pattern. A homozygosity mapping approach has thus far failed to unearth the responsible gene as the region shared by these three sibs is 27.7 Mb in size and contains over 200 genes with no obvious candidate. © 2014 Wiley Periodicals, Inc.